Development of Point Counter Point-Based Teaching Materials To Increase Speaking Ability in Debate Material for Student of Darul Hikmah Islamic Boarding School in Asahan - Irhami Tanjung, Syahri; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to determine the Development of Teaching Materials Based onPoint Counter Point to Improve Speaking Ability in Debate Material in Class X Students of Madrasah Aliyah Pesantren Darul Hikmah Asahan Academic Year 2025/2026. This type of research is experimental research with Random Sampling. The population in this study was the entire class X which amounted to 30 students. The sample of this study amounted to 30 students divided into 6 groups, namely group I consisting of 5 students as a control class using the conventional model and group II consisting of 5 students using the Point Counter Point model. The technique used in determining the sample is a simple Random Sampling technique. The instrument used in data collection is an essay test. After the learning was completed, a post-test was obtained with an average result of the experimental class of 88.13 and the control class of 80. The results of the t-test obtained tcount = 5.60> ttable = 2.00, so the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, there is a Development of Point Counter Point Based Teaching Materials to Improve Debate Speaking Skills in Class X Students of Madrasah Aliyah Pesantren Darul Hikmah in the 2025/2026 Academic Year